Specifics Of Linguistic And Cultural Studies Methodology Represented By The Crash-Course Russian As S Foreign Language - Кудрявцева, Наталия; Павлова, Наталья (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The paper investigates specific features of linguistic and cultural studies methodology in teaching of Russian as a foreign language as exemplified in the special format of the crash-course. The course is aimed at the development of the effective use of communication skills of international students regardless of their language reference level. The main tasks of the course are to give information as well as concrete tools for better integration, to organize the teaching process based on the learner-centered approach, to offer space for the interaction and to support the motivation of learners. The intensity of the course is one of its peculiar features, that defines the choice of the teaching methods and influences the structure and contents of the course, for example, selection and distribution of the teaching material, types of exercises etc. The paper stresses, that the methodology of linguistic and cultural studies forms the basis of the whole teaching process and is represented in each group of the crash-course regardless of the level of Russian proficiency of learners.